Exploring the links between various traumatic experiences and ICD-11 PTSD and Complex PTSD: A cross-sectional study - Kairyte, Agniete; Kvedaraite, Monika; Kazlauskas, Evaldas; Gelezelyte, Odeta (Frontiers in Psychology, 2022)
Background. The 11th revision of the International Classification of Diseases (ICD-11) included two distinct trauma-related diagnoses – Posttraumatic Stress Disorder (PTSD) and Complex Posttraumatic Stress Disorder (CPTSD). The initial diagnostic factor for both disorders is exposure to a traumatic event. This study aimed to explore whether exposure to different traumatic experiences distinguish risk for PTSD and CPTSD. Methods. The study sample comprised 158 trauma-exposed participants, M(SD)age = 33.61(9.73). The Life Events Checklist-Revised (LEC-R) was used to evaluate trauma exposure, and the International Trauma Questionnaire (ITQ) was used to assess risk for ICD-11 PTSD and CPTSD. Multinomial logistic regression was used to determine traumatic events as predictors of risk for PTSD and CPTSD. Results. Analysis revealed that sexual abuse experienced in childhood or adulthood was associated with both PTSD and CPTSD. History of other unwanted sexual experiences and childhood physical abuse predicted CPTSD compared to PTSD, whereas exposure to natural disasters predicted PTSD compared to CPTSD. Conclusions. The results showed that experiences of certain traumatic events, such as sexual trauma, childhood physical abuse or natural disasters, might help distinguish risk for PTSD and CPTSD. Nevertheless, future studies on specific aspects of trauma exposure are necessary.